Why Can't Orphans Play Baseball? Writing Into the Primal Wound. (March 2021) - Dann, Mig; Fulton, Laura; Rogers, Christine; Harris, Anne
This article explores the loss, legacy, and liberatory possibilities of addressing adoption through collaborative autoethnographic writing. We invite readers, through critical autoethnographic narratives and scholarship, to engage with our lived experiences as both cultural and familial histories. The return to the pre-adoption place of origin will not give us the closure we seek, so here we explore the future-making potential of collective adoptee narratives. If home may be less of an origin and more of a destination, each of the four authors engages in this autoethnographic research as a creative and collaborative means of finding a way toward becoming-home.